Implementation of Character Education In Integrated Islamic Elementary School - Neliwati Neliwati; Muhammad Isa; Rija Ansari; Siti Rahma Qomaruddin Lubis (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
Institutions considering a wide range of non-educational behavior has now been penetrated in our educational institutions. Such behavior, among others: the phenomenon of violence, sexual abuse, mania business through schools, corruption and arbitrariness that occur among school. After conducting a reliminary study in Integrated Islamic Elementary School Anak Sholeh Hinai, Langkat it can be concluded while, that the Integrated Islamic Elementary School Anak Sholeh Hinai, Langkat is an educational institution that began to notice the importance of character education.This study used a qualitative descriptive approach. In collecting the data, the authors using observation, interviews, and documentation.This study produced three findings: first from the aspect of planning is done in several ways, including: a) Designing school conditions conducive, b) Designing curriculum of character education explicitly, c) Creating a curriculum characters integrative, d) Management of classrooms, e) environmental management outside the classroom. Both at the level of implementation is done, among others: a) Cooperation between the school community, b) Applying the model, c) Habituation pray, d) Guidance Qur’an intensive, e) Appreciating the creativity of learners, f) Establish a harmonious relationship between teachers and learners. Third at the level evalusinya do several things, among others: a) Cooperation with parents of learners (co parenting), b) strict supervision of the character, c) Home visit (Home Visits), d) Issue a communication book.